أثر التطور المالي على النمو الاقتصادي في الجزائر دراسة تحليلية قياسية للفترة 1995-2020 - مسعودة،شوقي; صبرينة،تواتي (university of eloued جامعة الوادي, 2024)
هدفت هذه الدراسة إلى قياس أثر التطور المالي على النمو الاقتصادي في الجزائر٬ باستعمال بيانات السلاسل الزمنية للفترة من سنة 1995إلى غاية ٬2020 وبوضع الاشكالية التالية: ما مدى الاثار التي يخلفها التطور المالي على مؤشر النمو الاقتصادي في الجزائر خلال الفترة1995-2020?٬ وللإجابة على ذلك تم استعراض الجانب النظري والتطبيقي لمتغيرات الدراسة٬ وذلك بالاعتماد على المنهج الوصفي٬ والمنهج التحليلي٬ حيث اشتملت هذه الدراسة على مؤشرين خاصين بالتطور المالي هما نسبة المعروض النقدي إلى اجمالي الناتج نسبة القروض الموجهة للقطاع الخاص إلى اجمالي الناتج المحلي كمتغيرات مستقلة٬ ومعدل النمو الاقتصادي كمتغير تابع٬ والانفتاح التجاري كمتغير ضابط٬ وذلك بالاعتماد على نموذج الانحدار الذاتي ذات الفجوات الزمنية المتباطئةARDL٬ وقد توصلت الدراسة إلى وجود علاقة توازنية طويلة الأجل بين المتغيرات عند مستوى معنوية5%٬ إلا أن القروض الموجهة للقطاع الخاص إلى اجمالي الناتج المحلي الإجمالي كان لها تأثير غير معنوي على النمو الاقتصادي٬ كما أظهرت الدراسة أيضا أن كل المتغيرات لها تأثير سلبي على النمو الاقتصادي٬ كما للنموذج قدرة تفسيرية عالية R2=77%)) . This study aimed to measure the impact of financial development on economic growth in Algeria, using time series data for the period from 1995 to 2020, and by setting the following problem: What is the extent of the effects that financial development has on the economic growth index in Algeria during the period 1995-2020?, and to answer the questions. The theoretical and practical aspects of the study variables were reviewed, relying on the descriptive approach and the analytical approach. This study included two indicators of financial development: the ratio of the money supply to the total output, the ratio of loans directed to the private sector to the gross domestic product as independent variables, and the economic growth rate as a variable. Continued, and trade openness as a control variable, based on the autoregressive model with slow time lags (ARDL). The study found that there was a long-term equilibrium relationship between the variables at a significance level of 5%. However, loans directed to the private sector to the total gross domestic product had an insignificant effect. On economic growth, the study also showed that all variables have a negative impact on economic growth, and the model has a high explanatory power (R2 = 77%).
مذكرة ماستر علوم اقتصادية
Keywords: تطور مالي٬ نمو اقتصادي٬ اقتصاد جزائري٬ بيانات السلاسل الزمنية٬ نموذجARDL. : financial development; economic growth; Algerian economy; time series data; ARDL model.